(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
Michel Lejeune, author of Celtiberica in 1955, introduced the first Botorrita bronze to the French scientific community by including it in his seminar programme at the École Pratique des Hautes Études in September 1973, just a few months after its discovery. Since 1985, this scholar has also been responsible for the Recueil des inscriptions gauloises (RIG), a collection of Gaulish inscriptions found in France. His encyclopaedic knowledge of the different languages and scripts of the Mediterranean basin has made him a key figure in the study of fragmentary languages. Following in his footsteps, we can see how research in this field has progressed and how it is currently being extended on both sides of the Pyrenees.